Teacher Competence Improvement Training in Writing Best Practice Using The Special Projects Assignments Method For ‘MGMP’ SMA Pesisir Selatan - Yetty Zainil; Arnellis Arnellis (Pelita Eksakta, 2022)
This paper aims to report the result of the training to increase teacher competence in writing Best Practices with the Special Projects Assignments Method and developing competent teachers who can write articles and their impact on sustainable competency development. The methods used in the service of participatory methods are offline and online. This training phase begins offline by administering questionnaires, and designing problems, then followed by providing Best Practices writing technique skills offline; discussion at the end of the training carried out online. The training results show that the competence of senior high school teachers in Pesisir Selatan has increased in writing best practice reports, with only one person (5%) still needing to submit didn’t draft required. This increase was also supported by the success of two training participants from SMAN 3 Painan, namely Zulmariko, in the 3rd place, and Darma Yunita, who was selected as the finalist in the best practice contest in the Province of West Sumatra on November 2022.